The postnatal morbidity associated with second-trimester miscarriage. (1st September 2016) - Morris, Aoife; Meaney, Sarah; Spillane, Niamh; O'Donoghue, Keelin
Abstract: Objective(s) : To describe the complications, and their incidence, associated with the management and delivery of a distinct second-trimester miscarriage cohort. Methods : A retrospective cohort study was undertaken in a large, tertiary-referral university hospital (8500 deliveries per annum). All cases of pregnancy loss occurring between 14 +0 and 23 +6 were identified from July 2009 to June 2013 ( n  = 181). Medical notes were reviewed and the number of complications among this cohort was identified. Logistic regression was conducted to assess associations with clinical presentation and management. Results : The mean gestation of loss was 18 +2 weeks (SD: 2 +2 ). 64.6% ( n  = 117) of the total losses were of intrauterine fetal demise (IUFD) with 17.7% ( n  = 32) following preterm premature rupture of membranes (PPROM) and 17.7% ( n  = 32) following preterm labour (PTL). All women required inpatient admission with 59.1% ( n  = 107) undergoing medical induction of labour. PPROM cases, compared with cases of IUFD, had increased odds of requiring antibiotic therapy (OR 13.75, 95% CI: 4.88–38.72) and readmission (OR OR 4.15, 95% CI 1.12–15.36). Conclusion : These women represent a small proportion of the obstetric population but remain a distinct cohort whose management is complicated by high rates of morbidity requiring medical intervention. An awareness of these risks should inform future clinical practice.